Efficiency assessment of hybrid Constructed Treatment Wetland System (CTWS) in treating domestic wastewater of Gawad Kalinga Fishermen's Village, Bayawan City - Cabanag, Fraulien Cabanban ([Cebu City] University of the Philippines Visayas-Cebu College, 2008)
This study investigated the efficiency of on-site hybrid constructed treatment wetland system (CTWS) planted with Phragmites karka, in treating domestic wastewater of Gawad Kalinga fishermen's Village, Barnagay Villareal, Bayawan City, in terms of percent change in pH, percent removal in DO, TDS, TSS, COD,NH3-N, and TP, and cost-effectiveness of the CTWS in comparison with a sequencing batch reactor (SBR) to levels that conform to the effluent discharge regulatory standards for coastal and marine waters. Results showed that the percentage change in pH was 3.88 + 2.28 and the percent removal of TDS, TSS, COD,NH3-N and TP were 49.29 + 4.44 ; 10.57 + 13.3795.76+ 1.68, 99.89 + 0.02, and 97.37 + 1.66, respectively, at mean residence time of 52 hours. Apparently, the change in DO was negligible (from 0 to 0.8mg/L). The effluent pH and COD mean values passed the discharge regulatory standards of DENR except for TSS and DO. Currently, no DENR regulatory standards are available for NH3-N ,and TP for coastal waters. The effluent NH3-N concentration exceeded the coastal and marine water quality criteria for the ASEAN region. The treatment wetland system was found to behighly efficient in removing organic matter and nutrients in the wastewater as indicated by the high percent removal in COD (95.76%), NH3-N (99.89%) and TP (97.37%). However, theremoval efficiency for TDS was moderately high (49.32%) and low for TSS (10.62%). The CTWS removal efficiencies for nutrients and COD were comparable with those of the SBR except forTSS. The total cost/year capita for CTWS, based on the results, amounted to PhP 464. The SBR was PhP 2,259, based on available literature. The CTWS was cost-effective compared to theproposed SBR at Sabang, Puerto Galera, Mindoro, by PhP 1,794/year-capita in reducing pollution load in domestic wastewater to levels that conform to effluent discharge regulatorystandards. A user fee collection of Php 464/year-capita (PhP 39/month-capita or PhP 1.30/day-capita) is both affordable on the part of the government to invest and construct CTWS, and fousers to pay for the service provided by the wetland system. The CTWS has ancillary benefits that are absent in the SBR, The CTWS provides habitat for various resident and transient bird species, forms an aesthetically pleasing and functional landscape, provides opportunities for formal and informal education on caring for the environment, and provides opportunities for tourism and recreational activities, making the CTWS a more cost-effective waste management option in treating domestic wastewater than SBR.
Thesis (M. S. Environmental Studies) -- [Cebu City] : U. P. Visayas-Cebu College, May 2008.